A Pulmonary Zebra: Adult Primary Pulmonary Synovial Sarcoma - Sheffield Sandra; Nwachukwu Chidi; Ashby Tracy (Case Reports in Oncological Medicine)
Primary pulmonary synovial sarcoma (PPSS) is an extremely rare tumor, with approximately 50 cases being reported in the English literature (Golota et al., 2018). Difficulties are often encountered in the diagnosis of PPSS as it can be confused with other spindle or round cell tumors, such as fibrosarcoma, hemangiopericytoma, mesothelioma, sarcomatoid carcinoma, or metastatic sarcomas. PPSS was first described by Zeren et al. in 1995. We present a case of PPSS in a 41-year-old woman, who complained of progressive dyspnea and left-sided chest pain.